United States of America. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in the United States during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as leadership, financing, biotechnology, economy, sustainability, resilience against climate change, agricultural development, policies , post-harvest loss management and pest control, such as coffee rust.